Penggunaan Mulsa Plastik dalam Budidaya Tanaman Kacang Panjang di Desa Sipahoras Lama Kecamatan Sosopan - Syahputra Harahap, Anggi Rizky; Siregar, Raja Aminuddin; Siregar, Emmi Juwita; Siregar, Jerry Maulana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The low productivity of long beans in Sipahoras Lama Village, caused by conventional cultivation systems lacking soil protection, poses a significant challenge to local food security. This Student Creativity Program (PKM) aims to introduce Silver-Black Plastic Mulch technology to address weed competition and microclimate fluctuations. The implementation method employed a participatory approach, encompassing problem identification, socialization, and technical training through the establishment of demonstration plots. The results indicated a significant improvement in the partners' skills in applying the technology independently. Agronomically, the use of mulch proved effective in suppressing weed growth, maintaining soil moisture stability, and producing healthier vegetative plant performance compared to control plots. It is concluded that this transfer of appropriate technology serves as an effective strategy to enhance farming efficiency and support sustainable village food self-sufficiency.